Meningkatkan Hasil Belajar Sejarah Kebudayaan Islam: Studi Tentang Pola Interaksi Edukatif Guru dan Siswa - Al-Hasy, Dhiva Munaya; Soiman; Enny Nazrah Pulungan (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2024)
The purpose of this study was to determine the pattern of educational interaction between teachers and students in learning the history of Islamic culture in improving learning outcomes. This type of research is qualitative research, data collection methods using observation, interviews, and documentation. Data analysis techniques through data reduction, data presentation, and drawing verification conclusions. The subjects of the study were Islamic cultural history teachers and the informants were the curriculum field, student representatives. The results of this study are the educational interaction patterns applied effectively. Islamic cultural history teachers use a one-way pattern in delivering material, a two-way pattern through question and answer interactions, and a three-way pattern with group activities. The three patterns that have been applied can have a positive impact on improving learning outcomes, as evidenced by students who are increasingly active in learning and have in-depth knowledge of the material, so that students fulfill three educational domains, namely cognitive, affective, and psychomotor.